Chiral transcription in self-assembled tetrahedral Eu4L6 chiral cages displaying sizable circularly polarized luminescence. Issue 1 (December 2017) - Yeung, Chi-Tung; Yim, King-Him; Wong, Ho-Yin; Pal, Robert; Lo, Wai-Sum; Yan, Siu-Cheong; Yee-Man Wong, Melody; Yufit, Dmitry; Smiles, Danil; McCormick, Laura; Teat, Simon; Shuh, David; et al.
Abstract Predictable stereoselective formation of supramolecular assembly is generally believed to be an important but complicated process. Here, we show that point chirality of a ligand decisively influences its supramolecular assembly behavior. We designed three closely related chiral ligands with different point chiralities, and observe their self-assembly into europium (Eu) tetrametallic tetrahedral cages. One ligand exhibits a highly diastereoselective assembly into homochiral (either ΔΔΔΔ or ΛΛΛΛ) Eu tetrahedral cages whereas the two other ligands, with two different approaches of loosened point chirality, lead to a significant breakdown of the diastereoselectivity to generate a mixture of (ΔΔΔΔ and ΛΛΛΛ) isomers. The cages are highly emissive (luminescence quantum yields of 16(1) to 18(1)%) and exhibit impressive circularly polarized luminescence properties (|g lum |: up to 0.16). With in-depth studies, we present an example that correlates the nonlinear enhancement of the chiroptical response to the nonlinearity dependence on point chirality. Controlling the chirality of self-assembled polyhedra is a synthetic challenge. Here, the authors stereoselectively form emissive lanthanide tetrahedral cages from a series of chiral ligands, and use their circularly polarized luminescence to explore the effect of ligand point chirality on supramolecular architecture.